PENGARUH VOLUME PEMBERIAN AIR TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Anis Tatik Maryani; Gusmawartati Gusmawartati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2010)
Oil palm (Elaeis guineensis Jacq.) is a plantation which plays an important role for Indonesia as the leading commodity for export or for the commodity that is expected to increase farmers' income. Of the various factors that cause the production of palm oil decreased by one of them is the problem of drought during the dry season as it is known that palm oil has a shallow root system (root fibers) so that the easy availability of water shortages. This research was carried out experimentally by using Completely Randomized Design (CRD) consisting of 4 (four) treatment with 3 (three) replications, so there are 12 experimental units. Each unit consists of Two plants were taken 1 (one) of plant samples. The tested combined treatment consisting of four levels: A (The Water 2400 ml Marihat D × P), B (Giving Water 2400 Topaz ml D × P), C (Provision of Water 1200 ml Marihat D × P), and D (Provision of Water 1200 ml of D × P Topaz). The parameters observed were plant height increment, number of leaves, corm girth increment, dry weight, seed quality index and proline content. The data obtained were analyzed using ANOVA and followed by further tests DNMRT at level 5%. Results showed that treatment of water supply volume provides significant results on the observation parameters plant height increment, whereas the parameters observed in the number of leaves, corm girth increment, dry weight, and seed quality index showed no significant results after further testing DNMRT at level 5%.